Pengembangan Strategi Keperawatan Komunitas untuk Meningkatkan Kesehatan Masyarakat di Wilayah dengan Akses Terbatas di Wilayah Desa Morano Kab. Mamuju Sulbar Tahun 2023 - Musdalifah, Musdalifah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Background: Morano Village, Mamuju Regency, West Sulawesi, is an area with limited access to health services. This results in low public health quality and limited treatment of both infectious and non-infectious diseases. Objective: This study aims to evaluate community nursing strategies developed to improve public health in areas with limited access to health care. Methods: This study used a descriptive qualitative design with a case study approach. Data were collected through in-depth interviews, field observations, and documentation. Informants included community nurses, health cadres, and the community. Data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. Results: The main strategies developed included enhancing family-based health promotion, establishing village health posts, training cadres, and utilizing simple telehealth for remote medical consultations. These interventions have been shown to increase community knowledge, increase immunization coverage, and reduce the number of visits for infectious disease cases. Conclusion: The development of community nursing strategies is effective in improving public health in areas with limited access to health care. Government support is recommended for strengthening community-based health facilities and infrastructure.